Politik Dinasti dalam Pandangan Islam - Rizki Syafril (Journal of Education on Social Science (JESS), 2020)
ABSTRAK This paper discusses the dynastic politics phenomena that occur according to the Islamic view. The political legitimacy of dynasties is not regulated in the Islamic political system, but in reality, dynastic political practices are widely applied in Islamic governments and in governments where the majority of the people are Muslim. This paper is a research library with data sources consisting of primary data and secondary data. While data analysis uses inductive, deductive and comparative methods. The results of the study concluded that dynastic politics according to Islam was permissible, if it was based on the conditions of the existing leader and must be by the appointment process exemplified by prophet and prophet's best friend and a leader by the expectations of the people and the leader was an expert in his field. While dynastic politics should not be if a leader is a person or group will and is not an expert as a leader and puts personal or group interests first. Keywords: dynastic politics, Islamic political, leader, Islamic governments